Testing of the California Bearing Ratio (CBR) on the Bottom Foundation (LPB) Airport of Okaba District - Yance Kakerissa (Global Writing Academica Researching & Publishing, 2022)
Okaba Airport is one of the airports situated in Okaba District, Merauke Regency. The soil conditions in the Okaba District are soft. This airport requires the development and construction of airport amenities, including runway extension, taxiway development, and airport apron enlargement, in this instance the runway. This research utilized Okaba District subbase material. This study uses local materials to determine how much the CBR value is at LPB Okaba Airport. This research uses using experimental method. The tests included testing the physical properties of the original soil and local sand mixture from the Okaba district, including specific gravity, water content, bulk density, and grain distribution, and testing the mechanical properties of the original soil, including compaction testing and testing the California Bearing Ratio laboratory using local sand added materials. In the CBR test, the mixed soil is examined immediately, without curing. Based on the results of evaluating the physical qualities of the soil type at the location of the Okaba Kampung Wambi District, in accordance with AASTHO's hand drill results. The soil is class A-3, with fine sand as the predominant material, and the CBR value of the original soil load value of 0.1 in is 5% and the load value of 0.2 in is 4%; the results of the original soil CBR test added 10% sand added 10%, then 10% sand added material and 5% PC was 36%, then 10% sand added material, and 7% PC by 80%, and finally 10% sand and 9% PC by 85%.